Journalism in the Age of Digital Autocracy: A Comparative ASEAN Perspective - Aim Sinpeng; Youngjoon Koh (JAS (Journal of ASEAN Studies), 2022)
Cyber authoritarianism is on the rise globally. Governments around the world are seeking innovative ways to monitor, surveil, censor and persecute government critics, activists and journalists. Southeast Asia is an especially hostile environment for journalism online: its governments have regularly investigated, arrested and convicted ordinary citizens for their online activities. The region also remains one of the most dangerous places for journalists in the world. This raises the question of if and how news organisations survive and thrive in this increasingly repressive environment. The study draws on original survey and interview datasets of 52 digital news organisations in Indonesia, Malaysia, Philippines and Thailand conducted as part of the 2021 Inflection Point International project on digital media entrepreneurship in Latin America, Southeast Asia and Africa. We argue that digital news organisations in Southeast Asia continue to report and investigate politically and socially sensitive issues despite the high risks for state repression. They are motivated by their belief in providing public good and supporting civic engagement. The findings in this study provide concrete empirical evidence that digital authoritarianism does not exert downward pressure on critical journalism.